Identification of alkyl guaiacyl dehydroabietates as novel markers of wood tar from Pinaceae in archaeological samples. (October 2016) - Bailly, Lucile; Adam, Pierre; Charrié, Armelle; Connan, Jacques
Highlights: Alkyl guaiacyl dehydroabietates in archaeological samples identified via synthesis. Formed by reaction of lignin pyrolysis products and dehydroabietic acid. They are unambiguous markers of wood tar from Pinaceae. Abstract: Resinous material from conifers from the Pinaceae family is frequently found in an archaeological context. The material was used, notably, as waterproofing agent, as adhesive or for the caulking of boats. Two main types of material can be distinguished: resin, the exudate of conifer trees, and wood tar obtained by dry distillation of wood. Molecular investigation of such material aims, notably, at developing new molecular tools for the determination of the biological and geographical origin or of the manufacturing techniques, and for the discrimination between resin and wood tar. In this context, we report the identification by synthesis of alkyl guaiacyl dehydroabietates, which occur in a series of recent and archaeological conifer wood tar samples from shipwrecks and Gallo-Roman tar preparation sites. They most likely result from the reaction of dehydroabietic acid and alkyl guaiacols, the latter being typical wood pyrolysis products formed during the preparation of wood tar. Alkyl guaiacyl dehydroabietates are therefore proposed to be specific molecular markers for conifer wood tar, allowing a clear molecular distinction between this material and resin to be made. They are also more resistant to the alteration undergone by archaeological samples than other compounds previously proposed as markers of conifer wood tar such as anhydrosugars or alkyl guaiacols.